Structure, gelation, and antioxidant properties of curcumin-doped casein micelle powder produced by spray-drying. Issue 2 (11th January 2018) - Khanji, Aya N.; Michaux, Florentin; Petit, Jeremy; Salameh, Dominique; Rizk, Toufic; Jasniewski, Jordane; Banon, Sylvie
Abstract : The encapsulation of curcumin in micellar caseins (MCs) and the production of powder were performed by spray-drying. Abstract : The encapsulation of curcumin in micellar caseins (MCs) and the production of powder were performed by spray-drying. Nearly 97% of the curcumin was retained and the yellow powder showed a typical high casein powder morphology. The hygroscopic properties were determined, slight differences reflected less available hydrophobic sites when curcumin was bound to casein, favoring interactions with water in curcumin-enriched MC powders. No difference was detected on the internal MC structure via SAXS. The antioxidant activity of doped-curcumin powder presented 88% of active curcumin. For 60 days at 40 °C storage, the antioxidant activity of curcumin measured by ABTS and FRAP assays was preserved with a percentage of 82 ± 2.0% and 84 ± 1.1%, respectively. Curcumin doped powders presented similar features to classical casein powders (rehydration and gelling abilities). It was demonstrated that curcumin encapsulation in MCs in its powder form helped in protecting its antioxidant activity without influencing the techno-functional properties of MCs. This study allowed the incorporation of curcumin via the MC matrix as an active food ingredient available in a powder state usable as classical milk powder in several food formulations.